1974
DOI: 10.1177/070674377401900219
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatry and Oncology: A Review

Abstract: There are complex relationships between cancer and mental state, of which the most readily understandable are the psychological reactions of patients with established malignant disease. More speculative, and difficult to study, is the possibility that psychological states may predispose to the development of cancer. Currently, theoretical and research interest centres on a third topic — the high frequency of cases in which an underlying malignant disease presents as a ‘functional’ psychiatric illness, usually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1977
1977
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The question of causal direction is not at issue in this review. (For a review of the psychosomatic research see Bacon, Renneker, & Cutler, 19S2;Brown, Narsamis, Toews, & Shane, 1974;Fox, 1978;Goldfarb, Drieser, & Cole, 1967;Headley, 1977;Kissen, 1969;LeShan, 1959;Miller, 1977;Mitchell, 1967;Perrin & Pierce, 1959;Surawicz, Brightwell, Weitzel, & Othmer, 1976. ) Authors have suggested that a possible remedy for this state of affairs might be found in providing medical staff with some knowledge as to the likely psychological reactions to breast cancer (Crary & Crary, 1974;Rickel, 1973;Senescu, 1963).…”
Section: Psychological Impact Of Cancermentioning
confidence: 99%
“…The question of causal direction is not at issue in this review. (For a review of the psychosomatic research see Bacon, Renneker, & Cutler, 19S2;Brown, Narsamis, Toews, & Shane, 1974;Fox, 1978;Goldfarb, Drieser, & Cole, 1967;Headley, 1977;Kissen, 1969;LeShan, 1959;Miller, 1977;Mitchell, 1967;Perrin & Pierce, 1959;Surawicz, Brightwell, Weitzel, & Othmer, 1976. ) Authors have suggested that a possible remedy for this state of affairs might be found in providing medical staff with some knowledge as to the likely psychological reactions to breast cancer (Crary & Crary, 1974;Rickel, 1973;Senescu, 1963).…”
Section: Psychological Impact Of Cancermentioning
confidence: 99%
“…Patients whose cancer is expressed through the unconscious before diagnosis may unconsciously expect to die, despite medical advancements which show that early breast cancer detection leads to greater cancer cure. As shown by Locke et al [24], Selye [25], and Brown et al [26], the immune system, personality, and emotional expression may all interact to affect one's ability to fight illness. Therefore, negative unconscious psychological beliefs may rein force an already diseased physical condition and sabotage potentially helpful medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly a great deal needs to be done before we gain more than a minimum of understanding of the nature of cancer-brain interactions. As Brown et al (1974) have remarked, 'There are complex relationships between cancer and mental state of which the most readily understandable are the psychological reactions of patients with established malignancy. More speculative .…”
Section: R---------------------------------------mentioning
confidence: 99%